Oriented growth of Bi3.25La0.75Ti3O12 thin films on RuO2/SiO2/Si substrates by using the polymeric precursor method: Structural, microstructural and electrical properties - Simoes, A. Z.; Ramirez, M. A.; Riccardi, C. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer, 2007)
c-axis oriented Bi3.25La0.75Ti3O12 (BLT) thin films were grown on a RuO2 top electrode deposited on a (100) SiO2/Si substrate by the polymeric precursor method. X-ray diffraction and atomic force microscope investigations indicate that the films exhibit a dense, well crystallized microstructure having random orientations with a rather smooth surface morphology. The electrical properties of preferred oriented Bi3.25La0.75Ti3O12 (BLT) thin films deposited on RuO2 bottom electrode leaded to a large remnant polarization (P-r ) of 17.2 mu C/cm(2) and (V-c ) of 1.8 V, fatigue free characteristics up to 10(10) switching cycles and a current density of 2.2 mu A/cm(2) at 5 V. We found that the polarization loss is insignificant with nine write/read voltages at a waiting time of 10,000 s. Independently of the applied electric field the retained switchable polarization approached a nearly steady-state value after a retention time of 10 s.
Keywords: thin films; atomic force microscopy; dielectric properties; fatigue